Modelling of ICAM-1 and LFA-1 interaction using molecular recognition theory - Štambuk, Nikola (Array, 2008)
Summary: The model of ICAM-1 and LFA-1 molecular interaction was used to test the application of the Molecular Recognition Theory for the identification of several discontinuous binding regions, i.e. ligand-receptor sites, within large antigenic molecules. Molecular Recognition Theory is an applicable heuristic algorithm for identification of possibly interacting amino acid pairs in short linear epitope/paratope sites within larger molecules. However, in order to achieve better efficiency this heuristic algorithm of molecular recognition has to be combined to several other procedures: molecular hydropathy analyses, secondary structure prediction methods and protein database search. The limitation of the combined MRT-hydropathy analyses is in the fact that it cannot explain 3D protein interactions, but it can be a valuable starting point for a more complex computational and experimental analysis